ANALYSIS OF THE DENSITY AND COMBUSTION RATE OF BRIQUETTE BASED ON THE COMPOSITION OF PEANUT SHELL AND COCONUT SHELL INGREDIENTS: ANALISIS DENSITAS DAN LAJU PEMBAKARAN BRIKET BERDASARKAN KOMPOSISI BAHAN PENYUSUN KULIT KACANG TANAH DAN TEMPURUNG KELAPA - Yusraida Khairani Dalimunthe Rani; Djoko Sulistyanto; Syamsul Irham; Thariq Madani; Teuku Ananda Rizky (INTAN Jurnal Penelitian Tambang, 2023)
The study's purpose was to analyze the density value and the burning rate of briquettes made from a combination of peanut shell and coconut shell ingredients with a fixed amount of starch adhesive concentration. The briquette making involves processing peanut shells and coconut shells, grinding and 60 mesh sifting, mixing with adhesive, printing, and drying in an oven (1200C for ± 30 minutes). The samples tested were the composition of peanut shells (K) and coconut shells (T). The combination of two briquette materials has the same mass of 100 gr for each sample. The samples were made with several compositions, namely K1 (T = 90, K = 10), K2 (T = 80, K = 20), K3 (T = 70, K = 30), K4 (T = 60, K = 40 ), K5 ( T = 50, K = 50), K6 ( T = 40, K = 60), K7 ( T = 30, K = 70). The results showed that the highest density value was obtained from the K7 composition, which means it is composed of 30 gr coconut shell and 70 gr peanut shell with a density value of 0.292 gr/cm3 and the lowest density value obtained from the K3 composition, which means it is composed of 70 gr coconut shell and 30 grams of peanut skin with a density value of 0.170 gr/cm3. The longest flame time of the briquettes, until they go out and turn into ashes, is obtained from composition K1, which means it is composed of 90 grams of coconut shell and 10 grams of peanut shell with a flame time of 88 minutes, and the shortest time of the burning of briquettes until it goes out and turns into ashes is obtained from composition K5 which composed of 50 grams of coconut shell and 50 grams of peanut shell with a burning time of 57 minutes. The longest burning rate of briquettes, until they were extinguished and turned into ashes, was obtained from samples K3 and K5 with a burning rate of 125.6 cm3/minute, then the shortest burning rate of briquettes until they were extinguished and turned into ashes was obtained from samples K4 with a burning rate of 108.518 cm3/minute.